A molecule‐based genetic association approach implicates a range of voltage‐gated calcium channels associated with schizophrenia. Issue 4 (28th April 2018) - Li, Wen; Fan, Chun Chieh; Mäki‐Marttunen, Tuomo; Thompson, Wesley K.; Schork, Andrew J.; Bettella, Francesco; ,; Djurovic, Srdjan; Dale, Anders M.; Andreassen, Ole A.; Wang, Yunpeng
Abstract : Traditional genome‐wide association studies (GWAS) have successfully detected genetic variants associated with schizophrenia. However, only a small fraction of heritability can be explained. Gene‐set/pathway‐based methods can overcome limitations arising from single nucleotide polymorphism (SNP)‐based analysis, but most of them place constraints on size which may exclude highly specific and functional sets, like macromolecules. Voltage‐gated calcium (Cav ) channels, belonging to macromolecules, are composed of several subunits whose encoding genes are located far away or even on different chromosomes. We combined information about such molecules with GWAS data to investigate how functional channels associated with schizophrenia. We defined a biologically meaningful SNP‐set based on channel structure and performed an association study by using a validated method: SNP‐set (sequence) kernel association test. We identified eight subtypes of Cav channels significantly associated with schizophrenia from a subsample of published data ( N = 56, 605), including the L‐type channels (Cav 1.1, Cav 1.2, Cav 1.3), P‐/Q‐type Cav 2.1, N‐type Cav 2.2, R‐type Cav 2.3, T‐type Cav 3.1, and Cav 3.3. Only genes from Cav 1.2 and Cav 3.3 have been implicated by the largest GWAS ( N = 82, 315). Each subtype of Cav channels showed relatively high chip heritability, proportional to the size of its constituent gene regions. The results suggest that abnormalities of Cav channels may play an important role in the pathophysiology of schizophrenia and these channels may represent appropriate drug targets for therapeutics. Analyzing subunit‐encoding genes of a macromolecule in aggregate is a complementary way to identify more genetic variants of polygenic diseases. This study offers the potential of power for discovery the biological mechanisms of schizophrenia.